Anomaly and intrusion detection systems for smart grids - Abasıkeleş-Turgut, Ipek; Daş, Resul (Elsevier, 2024)
Smart Grid (SG) offering many advantages such as customer demand management, energy saving and minimizing losses by integrating information technology to the traditional electricity grid, is open to various attacks from inside and outside due to the nature of communication. In SG, which has a very complex structure, it is necessary to detect and remove attacks on a component basis. For this purpose, there are many studies on IDS in SG in literature. In this study, a total number of 58 SCI journal articles published between 2017 and 2023 for common SG components have been analyzed in detail. Both component-based and general evaluations are made on various system parameters. It is thought that this study will lead to new IDS techniques in the field of SG. © 2025 Elsevier Inc. All rights reserved.
Keywords: Anomaly detection; IDS; Smart grid security